1980
DOI: 10.2136/sssaj1980.03615995004400050045x
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical Characteristics and Transformations of a Vertical Rock‐Saprolite‐Soil Sequence in the North Carolina Piedmont: II. Feldspar Alteration Products‐Their Transformations Through the Profile

Abstract: Feldspar minerals near the rock‐saprolite interface weathered directly to gibbsite, tubular halloysite, and amorphous aluminosilicate minerals. The gibbsite precipitated as aggregates of tiny plates deep in the profile. This mineral then resilicated into a tabular halloysite pseudomorphic after the gibbsite.There was very little evidence of amorphous materials throughout the profile but apparently amorphous spheres formed on the surface of feldspars and quartz in the weathering rock. These amorphous spheres se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The decrease of the halloysite to kaolinite ratio toward the soil surface is also described in other studies (Calvert et al, 1980;Churman, 1990) and is ascribed to dehydration (Churchman and Gilkes, 1989). The results show no relation between halloysite-kaolinite PHR and the vegetation ( Table 6).…”
Section: Clay Fraction Mineralogysupporting
confidence: 77%
“…The decrease of the halloysite to kaolinite ratio toward the soil surface is also described in other studies (Calvert et al, 1980;Churman, 1990) and is ascribed to dehydration (Churchman and Gilkes, 1989). The results show no relation between halloysite-kaolinite PHR and the vegetation ( Table 6).…”
Section: Clay Fraction Mineralogysupporting
confidence: 77%
“…During late winter and spring, the high elevation soils experience intense leaching by cold, Sipoor waters that may foster microsites of low Si activity and gibbsite formation. On the other hand, Calvert et al (1980) argued that gibbsite, formed by alteration of feldspars in a gneissic saprolite, was essentially re-silicated to halloysite or kaolinite in upper soil horizons via dissolution of quartz. Given the dacitic to rhyolitic composition of the more recent Lassen ashes that most strongly influence the WF-3 and RF-4 pedons, it seems reasonable that gibbsite produced near the rock-soil interface is unstable closer to the surface due to silica released during weathering of the Si-rich ash.…”
Section: Phyllosilicates and Oxyhydroxidesmentioning
confidence: 99%
“…Several studies have found a decrease in the abundance ofhalloysite relative to that of kaolinite with an increase in degree of weathering of softs or with increasing proximity to the surface of soil profiles (Shimuzu, 1972;Eswaran and Wong, 1978;Calvert et al, 1980;Hughes, 1980;Hewitt and Churchman, 1982), Hence, it is tempting to infer that halloysite transforms to kaolinite with weathering. The apparently continuous series of X-ray powder diffraction (XRD) patterns of Ross and Kerr (1934) and Brindley and Robinson (1946) showing increasing order from halloysite to highly crystalline kaolinite also suggest a natural progression between halloysite and kaolinite.…”
Section: Introductionmentioning
confidence: 99%